2019
DOI: 10.3390/ijerph16193533
|View full text |Cite
|
Sign up to set email alerts
|

The Psychophysiological Implications of Soundscape: A Systematic Review of Empirical Literature and a Research Agenda

Abstract: The soundscape is defined by the International Standard Organization (ISO) 12913-1 as the human’s perception of the acoustic environment, in context, accompanying physiological and psychological responses. Previous research is synthesized with studies designed to investigate soundscape at the ‘unconscious’ level in an effort to more specifically conceptualize biomarkers of the soundscape. This review aims firstly, to investigate the consistency of methodologies applied for the investigation of physiological as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 68 publications
2
61
0
1
Order By: Relevance
“…Nevertheless, physiologic measures are not commonly used and neither included within soundscape data collection methods by ISO 12913-2 standard. Previous research revealed the importance in coupling the objective and subjective assessments of the acoustic environment with the recording of objective physiological responses [54][55][56], as this helps in better understanding the relationship between the physical acoustic environment and people´s perceptual and behavioral response to it. Physiological measurements should thus be included within soundscape assessment practices and further research efforts would be needed to investigate the association between sound stimuli, physiological responses, subjective assessments and behavioral reactions in the peculiar case of indoor environments.…”
Section: Methods For Indoor Acoustic Environment Perceptual and Physmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, physiologic measures are not commonly used and neither included within soundscape data collection methods by ISO 12913-2 standard. Previous research revealed the importance in coupling the objective and subjective assessments of the acoustic environment with the recording of objective physiological responses [54][55][56], as this helps in better understanding the relationship between the physical acoustic environment and people´s perceptual and behavioral response to it. Physiological measurements should thus be included within soundscape assessment practices and further research efforts would be needed to investigate the association between sound stimuli, physiological responses, subjective assessments and behavioral reactions in the peculiar case of indoor environments.…”
Section: Methods For Indoor Acoustic Environment Perceptual and Physmentioning
confidence: 99%
“…Higher NO2 exposure was related to an increased likelihood to report high noise annoyance, but the impact depended on traffic noise level, thus suggesting an interaction effect. In detail, the effect of NO2 resulted stronger in people exposed to low levels of noise (DNL ≤ 45 dBA) than in people exposed to medium noise levels (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). As a result, the authors suggest that a multiplier reduction in noise annoyance can be achieved through a simultaneous reduction of NO2 levels and noise levels [35].…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residementioning
confidence: 99%
“…A better understanding of contextual factors and aspects related to the interactions between people and places is required to characterize soundscapes holistically, as pointed out by Hermida and colleagues [16] in their case studies in Lisbon and Bogotá. For this purpose, it is certainly useful to review the corpus of literature looking at the positive effects that soundscapes and environmental sounds more generally can have on people's quality of life and well-being [17,18].…”
Section: Extending the Research Scope To More Soundscape Quality Dimementioning
confidence: 99%
“…The above physiological indicators have been widely used in research on risk perception and health in recent years, and have been shown to be able to sensitively reflect the physiological changes of individuals under stress. Because the alarm sound can be seen as a stress stimulus causing stress in the body or changes in the arousal level of the listener [38,39], and both EDA and heart rate are physiological indicators that rapidly respond to physiological arousal and stress stimuli [40][41][42], the mean SC score and heart rate would increase significantly under virtual stress stimulation, which are effective indicators of physiological response under stress stimulation [43]. SCL and SCR are also used to measure risk perception [44].…”
Section: Physiological Measurementsmentioning
confidence: 99%